MODUS OPERANDI OF ORGANIZED CRIME. VIOLENCE, CORRUPTION AND MONEY LAUNDERING - Cara, Arben (European Scientific Journal, ESJ, 2015)
The most typical characteristics like the use of violence, corruption and money laundering shape the modus operandi of organized crime. The use of violence and intimidation against victims, against members of groups inside the same organization or against members of other organizations, has been defined as an ingredient of Mafioso behavior, which brings as result the ‘law of silence’, and it consists in the duty of associates to keep silent about the secret. The use of influence and corruption in politicians, the public administration, the criminal justice system and private sector representatives is seen as a tool of the organized crime (groups) that facilitates their operations. The long process of money laundering is composed of combine and cover activities in one side, and the use of facilitators on the other side. Showing the modus operandi of organized crime constitutes the main aim of the work.